(untitled) (Revista Contexto & Saúde, 2026)
Objective: To validate the educational health content of the glossary of technical terms related to pregnancy, childbirth, puerperium, breastfeeding, and neonatology, according to expert judges. Methodology: Methodological research with 23 nurses, who were recruited through the virtual snowball method. Data collection took place in June and July 2024, using the Educational Health Content Validation Instrument, made available on Google Forms. The obtained data were submitted to content analysis. Results: The educational health content of the glossary was validated by expert judges, with a Content Validity Index (CVI) above 0.80 in all categories and a global CVI of 0.96. The feedback from the expert judges about the glossary indicates that it is educational, with clear and objective language, and light illustrations that spark the reader’s interest in the presented topics. Conclusion: It is organized and composed of the main information regarding the consultation of technical terms, presenting relevance and practical applicability not only for students during the teaching-learning process but also for health professionals working in the areas of gynecology and obstetrics, breastfeeding, neonatology, and pediatrics.